Assessment of Pollution Trend of Oke Afa Canal Lagos, Nigeria - R. A. Olowu; O. O. Ayejuyo; G. O. Adewuyi; I. A. Adejoro; T. A. Akinbola; M. O. Osundiya; C. T. Onwordi (E-Journal of Chemistry)
The physiochemical properties of Oke Afa water body were investigated. The parameters were compared with established international standard (APCELS). The canal water contained very high concentration of BOD (64.8±11.3 mg/L) and COD (107.8±22.3 mg/L) which would suggest the presence of a high level of organic load that result in the pollution of the canals. Significant concentration of TSS ranging from (92±100 mg/L), SO42- (9.84±5.59 mg/L), PO43- (0.66±0.33 mg/L), Cl (37±2.84 mg/L), NO3- (2.63±0.6 mg/L) and DO (0.96±0.15 mg/L) were observed. Low concentration of zinc and copper were observed except lead that has a higher concentration above the allowed permissible level at a point B of the sampling sites. Some heavy metals were not detected at all in all the sampled points of the canal. The pH and temperature were fairly constant and the values of conductivity reveal a slight decline in the ability of the water to conduct electricity down the canal. All the detected parameters fell within limits except Lead.